Web-based resources for comparative genomics - Gu Xun; Su Zhixi (Human Genomics, 2005)
Abstract The available web-based genome data and related resources provide great opportunities for biomedical scientists to identify functional elements in a particular genome region or to explore the evolutionary pattern of genome dynamics. Comparative genomics is an indispensable tool for achieving these goals. Because of the broad scope of comparative genomics, it is difficult to address all of its aspects in short survey. A few currently 'hot' topics have therefore been selected and a brief review of the availability of web-based databases software is given.